Origin of B chromosomes in the genus Astyanax (Characiformes, Characidae) and the limits of chromosome painting - Silva, Duilio M. Z. de A. [UNESP]; Daniel, Sandro Natal [UNESP]; Camacho, Juan Pedro M.; Utsunomia, Ricardo [UNESP]; Ruiz-Ruano, Francisco J.; Penitente, Manolo [UNESP]; Pansonato-Alves, Jose Carlos [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Oliveira, Claudio [UNESP]; Porto-Foresti, Fabio [UNESP]; Foresti, Fausto [UNESP] (Springer, 2016)
Eukaryote genomes are frequently burdened with the presence of supernumerary (B) chromosomes. Their origin is frequently investigated by chromosome painting, under the hypothesis that sharing the repetitive DNA sequences contained in the painting probes is a sign of common descent. However, the intragenomic mobility of many anonymous DNA sequences contained in these probes (e.g., transposable elements) adds high uncertainty to this conclusion. Here we test the validity of chromosome painting to investigate B chromosome origin by comparing its results for seven B chromosome types in two fish species genus Astyanax, with those obtained (1) by means of the physical mapping of 18S ribosomal DNA (rDNA), H1 histone genes, the As51 satellite DNA and the (AC)(15) microsatellite, and (2) by comparing the nucleotide sequence of one of these families (ITS regions from ribosomal DNA) between genomic DNA from B-lacking individuals in both species and the microdissected DNA from two metacentric B chromosomes found in these same species. Intra- and inter-specific painting suggested that all B chromosomes that were assayed shared homologous DNA sequences among them, as well as with a variable number of A chromosomes in each species. This finding would be consistent with a common origin for all seven B chromosomes analyzed. By contrast, the physical mapping of repetitive DNA sequences failed to give support to this hypothesis, as no more than two B-types shared a given repetitive DNA. Finally, sequence analysis of the ITS regions suggested that at least some of the B chromosomes could have had a common origin.
Keywords: B chromosome; rDNA; Satellite DNA; Microsatellites; Chromosome painting